If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -8)(x + -8) + -18 = -2 Reorder the terms: (-8 + x)(x + -8) + -18 = -2 Reorder the terms: (-8 + x)(-8 + x) + -18 = -2 Multiply (-8 + x) * (-8 + x) (-8(-8 + x) + x(-8 + x)) + -18 = -2 ((-8 * -8 + x * -8) + x(-8 + x)) + -18 = -2 ((64 + -8x) + x(-8 + x)) + -18 = -2 (64 + -8x + (-8 * x + x * x)) + -18 = -2 (64 + -8x + (-8x + x2)) + -18 = -2 Combine like terms: -8x + -8x = -16x (64 + -16x + x2) + -18 = -2 Reorder the terms: 64 + -18 + -16x + x2 = -2 Combine like terms: 64 + -18 = 46 46 + -16x + x2 = -2 Solving 46 + -16x + x2 = -2 Solving for variable 'x'. Reorder the terms: 46 + 2 + -16x + x2 = -2 + 2 Combine like terms: 46 + 2 = 48 48 + -16x + x2 = -2 + 2 Combine like terms: -2 + 2 = 0 48 + -16x + x2 = 0 Factor a trinomial. (4 + -1x)(12 + -1x) = 0Subproblem 1
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Subproblem 2
Set the factor '(12 + -1x)' equal to zero and attempt to solve: Simplifying 12 + -1x = 0 Solving 12 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12Solution
x = {4, 12}
| x*x-87=-5 | | 8y+12=4(y+5) | | 25-5m=4(m-5) | | 9+4d+5= | | 65x+98=9473213x-75431 | | 2x+x+5/7=5 | | 28+4w=-8 | | -81=x*x | | x+45=2x+15 | | -16=3(y-4)-7y | | 3(2q+5)=5(x+1q) | | x*x=-81 | | 4(2x-1)=2x+14 | | 10x+22=13x+10 | | 14x+14=36 | | 2x+5=8X+25 | | 4y+20-y-4=6 | | 5r^2+33r+40= | | 8(x-2)=40 | | 7-3x+9=5x | | -0.02x^2+1.4x-12=0 | | 6(b+5)+2=22+b | | x+10=43 | | -80000x+2000000=4200000 | | 13+8x=11-4 | | 5xn=400 | | -5(3+11n)=-10(10-3n) | | 11/2+12/6= | | -4x+10x=0 | | -80000x+2000000=3600000 | | 5(k-3)+6=-2k+12 | | ln(5)+ln(x-1)=0 |